Accumulation of Copper, Zinc, and Lead in Tilapia (Oreochomis spp. ) Under Laboratory Conditions - Ronny, Daud (Universiti Malaysia Sarawak (UNIMAS), 2007)
The uptake and elimination of copper (Cu), zinc (Zn) and lead (Pb) using tilapia during exposure to these metals was examined under controlled laboratory experiments. Tilapia (Oreoch romis spp. ) was acclimatized at 25+ 2° C (Room temperature) for 4 days. The tilapia was exposed to sublethal concentrations (LCso) of copper (Cu), zinc (Zn) and lead (Pb). The experiment was designed to allow four days of metal uptake and four days of depuration period. The tilapia was taken out at 24, 48, 72 and % hours for metal analysis. The water samples were tested daily and the water temperature of the experimental tanks were kept at 25+ 2° C and pH of 7.6 ± 0.1 was maintained. Accumulations of all metals increased with exposure time. Different rates of accumulation and depuration in tissue was found and this could be due to different mechanisms of metal binding and regulation. At the end of depuration, Zn levels in tissues of tilapia (Oreochromis spp. ) were higher than before exposure, while Cu and Pb levels in tissues were almost similar to levels at 24 hours of exposure. These results indicated that tilapia (Oreochromis spp. ) can be used as good biomonitoring organism of environment metals contaminant. The positive patterns, although different rates of accumulation and depuration for Cu, Zn and Ph support the use of tilapia (Oreochromis spp. ) as a biomonitoring agent for such metals.